Taxonomy and systematics: an essential underpinning of modern fisheries management - Livingstone, Mary (New Zealand Science Review, 2016)
​Accurate and reliable identification of the full range of fish and invertebrate species that are caught in New Zealand waters lies at the core of the fisheries Quota Management System (QMS). Species identification is required for accuracy of catch reporting and keeping track of quota by commercial fishers, for keeping to bag limits in the recreational and customary sector, and for compliance and sustainability purposes. It is also needed by many in the marine science community, particularly those in fisheries science. As New Zealand’s environmental obligations to national and international agreements continue to grow, accurate species identification has extended to non-QMS fish species, benthic invertebrates, and protected species. Furthermore, whole-fish identification is no longer sufficient, particularly where consumers require assurance that a fish in the kitchen has been caught from a sustainable source.